Formation Aspects of an Accessible Environment in Modern Landscape Architecture in Azerbijan - Karimov, Farid (Problemy Ekorozwoju, 2021)
Despite the recent complex reconstruction in Azerbaijan, public spaces, parks and boulevards still do not fully respond to inclusivity. A long-term comprehensive action plan should be developed, and targeted actions should be undertaken to address these short comings. Thus, in order to achieve full accessibility, equipment and construction should be carried out not only in parks, but also in public spaces, taking into account the needs and interests of people with different categories of disability. It is also necessary to improve the regulatory framework, to promote public awareness, to develop a positive attitude towards physically challenged people, and to train new generations of professionals to take action to ensure a high level of working on this field in the future.